P108 Service Evaluation - the impact and lessons learnt from the COVID-19 pandemic on a UK burns centre. (8th April 2021) - Phillips, Georgina; Talwar, Cyrus; Makaranka, Stanislau; Collins, Declan; Makaranka, Stanislau
Abstract: The COVID-19 pandemic has dramaticallyimpacted healthcare provision in the UK and burns services have had to adapt to ensure the continuityof a safe care. As we return to " normalit y" we reflect on lessons learnt from our response to this pandemic. A service evaluation was performed from patient notes between March 23rd and May8th 2020 and an anonymoussurveygiven to patients attending outpatient appointments. 258 patients were referred to our burns service and 148 patients completed the survey. Eleven burns were caused bytreatment or prevention of COVID-19. Patients delayed seeking medical attention due to concern of catching COVID-19 (36% adults, 8% children). There was a delayin referral of 17 patients despite them fulfilling the referral criteria. Infection rates were higher following delayed presentation (21% vs 6%). The majorityof burns were managed conservatively (237/258). Dressing changes were performed at home by32% of patients. The outreach team treated 22 patients. During the pandemic telemedicine has improved the efficiencyof outpatient burn care and outreach nurses have enabled treatment of vulnerable patients. More must be done to raise public awareness of preventable causes of burn injuryand to reassure them to seek help when burns occur.